2016
DOI: 10.1371/journal.pone.0152783
|View full text |Cite
|
Sign up to set email alerts
|

Salt Intake and Health Risk in Climate Change Vulnerable Coastal Bangladesh: What Role Do Beliefs and Practices Play?

Abstract: BackgroundHigh salt consumption is an important risk factor of elevated blood pressure. In Bangladesh about 20 million people are at high risk of hypertension due to climate change induced saline intrusion in water. The objective of this study is to assess beliefs, perceptions, and practices associated with salt consumption in coastal Bangladesh.MethodsThe study was conducted in Chakaria, Bangladesh between April-June 2011. It was a cross sectional mixed method study. For the qualitative study 6 focus group di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…102 The overall risk perception regarding excessive salt consumption is low and there is widespread belief that the cooking process can render the salt harmless. 103 High salt intake presumably contributes to hypertension, which is an established risk factor for CAD.…”
Section: Lifestyle Related Factorsmentioning
confidence: 99%
“…102 The overall risk perception regarding excessive salt consumption is low and there is widespread belief that the cooking process can render the salt harmless. 103 High salt intake presumably contributes to hypertension, which is an established risk factor for CAD.…”
Section: Lifestyle Related Factorsmentioning
confidence: 99%
“…Some families may consume an excess of salt in their diets, but most of the families seem to take permissible amount of salt. Because the amount of salt is divided by the number of family members, with equal weight given to everyone from old people to children, some individual salt intakes are likely to be underestimated, particularly for older people, who usually consume more salt (Rasheed et al 2016). Snacks were not considered, so the numbers shown here should be regarded as the minimum level of salt intake in the daily diet.…”
Section: Salt In Dietmentioning
confidence: 99%
“…As safe salinity levels in drinking water have not been suggested , except that sodium levels greater than 0.2 g/L are unacceptable in terms of taste (WHO 2008), the problem needs attention and the development of emergency countermeasures. In the past decade, studies on the impact of saline drinking water on health in Bangladesh were bolstered (Khan et al 2008(Khan et al , 2014Vineis et al 2011;Rasheed et al 2014Rasheed et al , 2016Talukder et al 2017). Khan et al (2011) studied the influence of saline water on pregnant women living in the coastal zones of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 It has been found that food consumption is dictated by beliefs and cultures. 7 In the UK, it has been found that a significant proportion of the respondents found themselves to be health conscious but they were not fully aware of the health issues regarding salt in the diet. 8 Review studies suggested that a greater number of women and those with higher education levels have higher levels of knowledge about salt intake.…”
Section: Introductionmentioning
confidence: 99%